2018
DOI: 10.1038/s41467-018-05472-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly directed one-step synthesis of [4]radialene on Cu(100) surfaces

Abstract: The synthetic challenges of radialenes have precluded their practical applications. Here, we report a one-step synthetic protocol of [4]radialene on a copper surface. High-resolution scanning tunneling microscopy measurements reveal that such catalytic reaction proceeds readily with high selectivity at the temperature below 120 K. First-principles calculations show that the reaction pathway is characterized by firstly the cooperative inter-molecular hydrogen tautomerization and then the C–C bond formation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…When the coverage increases up to θ ≈0.7 ML, additional DBA molecules break into the preceding hexagonally scattered phase (at θ ≈0.4 ML) in an interdigitating manner, eventually forming an isotropic porous honeycomb phase as shown in Figure c. During this polymorphic transition, the participating molecules first associate into tetramers by adjusting their point chirality, which possibly serve as nuclei to form the honeycomb phase (see Figure b). These results indicate that short‐range intermolecular interactions such as vdW and CH⋅⋅⋅π intermolecular attractions in balance with electrostatic intermolecular repulsions lead to the effective interdigitation of hydrogen atoms between adjacent molecules (see Figure a) . The C 3 symmetry of the six‐membered honeycomb unit results in organizational chirality, which is domain‐specific, as indicated in Figures d and S5.…”
Section: Resultsmentioning
confidence: 82%
“…When the coverage increases up to θ ≈0.7 ML, additional DBA molecules break into the preceding hexagonally scattered phase (at θ ≈0.4 ML) in an interdigitating manner, eventually forming an isotropic porous honeycomb phase as shown in Figure c. During this polymorphic transition, the participating molecules first associate into tetramers by adjusting their point chirality, which possibly serve as nuclei to form the honeycomb phase (see Figure b). These results indicate that short‐range intermolecular interactions such as vdW and CH⋅⋅⋅π intermolecular attractions in balance with electrostatic intermolecular repulsions lead to the effective interdigitation of hydrogen atoms between adjacent molecules (see Figure a) . The C 3 symmetry of the six‐membered honeycomb unit results in organizational chirality, which is domain‐specific, as indicated in Figures d and S5.…”
Section: Resultsmentioning
confidence: 82%
“…DFT calculations have revealed that the heptacene molecule acts as an electron acceptor and experimental results can be ascribed to the charge transfer between the substrate and molecules. Likely, tetraphenyl[4]radialene can be selectively prepared on Cu(100) from phenylacetylene . Different from the hexamers formed on Au(111), the tetramerization process is performed via a cooperative [1 + 1 + 1 + 1] cycloaddition mechanism.…”
Section: Controlling Surface Reaction Via Surface Manipulationmentioning
confidence: 99%
“…[4] Thec ycloaddition reaction by which cyclic ring structures are formed is an important tool to synthesize complex molecular species. [10] [2+ +2] cycloaddition takes place either in the intramolecular reaction of two tetra-aza-porphyrin derivatives, [11] and in the inter-molecular reaction of ortho-dihalotetracenes on Ag(111) and Cu(111). [10] [2+ +2] cycloaddition takes place either in the intramolecular reaction of two tetra-aza-porphyrin derivatives, [11] and in the inter-molecular reaction of ortho-dihalotetracenes on Ag(111) and Cu(111).…”
Section: Identifying Multinuclear Organometallic Intermediates In On-mentioning
confidence: 99%